Acceptability of self-collected vaginal samples for human papillomavirus testing for primary cervical cancer screening: comparison of face-to-face and online recruitment modes - Siew-Fei Ngu; Lesley SK Lau; Ching Yin Chan; Hextan YS Ngan; Annie NY Cheung; Karen KL Chan (BMC Public Health, 2024)
Abstract Background This study aimed to assess the acceptability and attitudes of women towards human papillomavirus (HPV) self-sampling and compare the effectiveness of two delivery modes utilising face-to-face and online website for cervical cancer screening in Hong Kong. Methods Women aged 30–65 years were invited to participate by distributing the study information pamphlets at the specialist clinics of a regional acute hospital. Those who were interested in participating were given the option to join directly face-to-face or through an online website. All participants provided informed consent and received self-sampling kits and acceptability questionnaires either immediately (face-to-face) or through the post after registering at the website (online). All participants were requested to collect their own vaginal samples using a swab which was then brushed on a DNA sample storage card and returned to the hospital either in person or by post. The self-collected samples were tested for high-risk HPV using the Sentis™ HPV assay, a validated isothermal nucleic acid amplification real-time fluorescent detection assay. The primary outcome was the uptake rate of HPV self-sampling. Results Of the 1998 women recruited (1200 face-to-face, 798 online), 1377 returned their samples, giving an overall uptake rate of 68.9%. The uptake rate was significantly greater in the face-to-face mode than in the online mode (74.6% vs. 60.4%, p < 0.001). The median age of the participants was 49 years, 43.7% were never or under-screened, and 7.1% had high-risk HPV detected. Overall, 82.1% of the participants reported self-sampling convenient, and 79.3% were not embarrassed when collecting self-samples. However, only 49.8% were confident that they had collected the self-samples correctly. Most (91.1%) of the participants expressed willingness to perform self-sampling again, mostly because it was simple (79.2%) and quick (56.3%). Conclusions HPV self-sampling can serve as an alternative primary screening method for cervical cancer in Hong Kong, especially for individuals who have not been adequately screened in the past. Both face-to-face and online website recruitment were associated with high acceptability, emphasising the potential benefits of utilising different platforms and strategies for reaching diverse populations.